ANALISIS EFISIENSI EKONOMI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHA TANI BAWANG MERAH LAHAN PANTAI DI DAERAH ISTIMEWA YOGYAKARTA - Heru Irianto; Sugiharti Mulya Handayani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2005)
The objective of this research is to find out economical efficiency of the use of production factors in sand-field onion on farm in Daerah Istimewa Yogyakarta. The method used in this research was Analytical Descriptive with Census Technique in implementation